Cefoxitin versus piperacillin–tazobactam as surgical antibiotic prophylaxis in patients undergoing pancreatoduodenectomy: protocol for a randomised controlled trial. Issue 3 (4th March 2021) - Nevarez, Nicole M; Brajcich, Brian C; Liu, Jason; Ellis, Ryan; Ko, Clifford Y; Pitt, Henry A; D'Angelica, Michael I; Yopp, Adam C
Abstract : Introduction: Although antibiotic prophylaxis is established in reducing postoperative surgical site infections (SSIs), the optimal antibiotic for prophylaxis in pancreatoduodenectomy (PD) remains unclear. The study objective is to evaluate if administration of piperacillin–tazobactam as antibiotic prophylaxis results in decreased 30-day SSI rate compared with cefoxitin in patients undergoing elective PD. Methods and analysis: This study will be a multi-institution, double-arm, non-blinded randomised controlled superiority trial. Adults ≥18 years consented to undergo PD for all indications who present to institutions participating in the National Surgical Quality Improvement Program Hepato-Pancreato-Biliary (NSQIP HPB) Collaborative will be included. Data collection will use the NSQIP HPB Collaborative Surgical Clinical Reviewers. Patients will be randomised to either 1–2 g intravenous cefoxitin or 3.375–4.5 g intravenous piperacillin–tazobactam within 60 min of surgical incision. The primary outcome will be 30-day postoperative SSI rate following PD. Secondary outcomes will include 30-day postoperative mortality; specific postoperative complication rate; and unplanned reoperation, length of stay, and hospital readmission. A subset of patients will have bacterial isolates and sensitivities of intraoperative bile cultures and SSIs. Postoperative SSIs and secondary outcomes will be analysed using logistic regression models with the primary predictor as the randomised treatment group. Additional adjustment will be made for preoperative biliary stent presence. Additionally, bacterial cultures and isolates will be summarised by presence of bacterial species and antibiotic sensitivities. Ethics and dissemination: This study is approved by the Institutional Review Board at Memorial Sloan Kettering Cancer Center. This trial will evaluate the effect of piperacillin–tazobactam compared with cefoxitin as antibiotic prophylaxis on the hazard of postoperative SSIs. The results will be disseminated regardless of the effect of the intervention on study outcomes. The manuscript describing the effect of the intervention will be submitted to a peer-reviewed journal when data collection and analyses are complete. Trial registration number: NCT03269994 .